An update on emerging therapeutic options for the treatment of trigeminal neuralgia. (2nd November 2017) - Obermann, Mark; Katsarava, Zaza; Holle, Dagny
ABSTRACT: Introduction : The successful treatment of trigeminal neuralgia (TN) remains a considerable challenge despite many currently available treatment options. Areas covered : Antiepileptic drugs, neuroleptic agents and muscle relaxants are most commonly used. All of them are unspecific and originally not developed for the treatment of TN. The response of the individual patient to any of these substances is quite variable and almost impossible to predict. This makes treatment of TN time consuming and sometimes unsuccessful. Expert opinion : Adequate placebo-controlled clinical trials were performed with carbamazepine in the 1960's and it is still considered the most effective drug. Emerging treatment options currently under clinical investigation are a novel sodium channel blocker (CNV1014802) that selectively blocks the Nav1.7 sodium channel, as well as local botulinum neurotoxin type A injections. Non-pharmacological options may include non-invasive electrical stimulation with transcranial direct current stimulation (tDCS), or repetitive transcranial magnetic stimulation (rTMS), which requires further evaluation for everyday use sustainability, however.